Body Perceptions and Psychological Well-Being: A Review of the Impact of Social Media and Physical Measurements on Self-Esteem and Mental Health with a Focus on Body Image Satisfaction and Its Relationship with Cultural and Gender Factors - Merino, Mariana; Tornero-Aguilera, José Francisco; Rubio-Zarapuz, Alejandro; Villanueva-Tobaldo, Carlota Valeria; Martín-Rodríguez, Alexandra; Clemente-Suárez, Vicente Javier (Healthcare (Basel), 2024)
This narrative review examines the interplay among body image perceptions, social media influence, physical measurements, and their impact on psychological well-being, focusing on the roles of cultural and gender differences and the need to understand the research methodologies employed in this field. In the age of digital proliferation, platforms like Instagram and Facebook have reshaped body image concerns, often leading to increased dissatisfaction and psychological distress due to constant exposure to idealized images and a culture of social comparison. Physical attributes such as weight, height, and BMI are scrutinized under societal standards of health and attractiveness, contributing to a spectrum of mental health issues including low self-esteem, depression, and eating disorders. This examination reveals how cultural norms and gender expectations further complicate body image perceptions, affecting individuals differently based on societal and personal ideals. It synthesizes current research and types of methods to illuminate how these factors together influence mental health and self-esteem, advocating for comprehensive interventions and policy measures aimed at mitigating body dissatisfaction and promoting a healthier, more inclusive understanding of body image. By delving into the complexities of body image satisfaction and its psychological implications, this review highlights the necessity of addressing these concerns within public health and social policy frameworks, underscoring the importance of a multifaceted approach to enhance individual and societal well-being.